Strengthen roles of commercial banks in vietnam economy– a case of eximbank - NGON, NGUYEN THI TUYEN; HUY, DINH TRAN NGOC; THANG, TRAN DUC (The journal of contemporary issues in business and government, 2021)
Is it the time for us to evaluate roles of Vietnam commercial banks and importance of risk management activities? This paper uses both quantitative analysis with statistical data and charts, combined with qualitative analysis including synthesis, inductive and explanatory methods in order to estimate and compare market risk via beta CAPM of Eximbank (EIB) and Asia Commercial Bank (ACB), 2 big listed joint stock banks in Vietnam. Research findings show us that market risk of Eximbank is higher and increase during post-low (L) inflation stage, compared to pre-L inflation time. Results may be used for policy implications and research models can be references for other countries including emerging markets.